GROUNDS FOR REFUSAL OF CONDITIONAL RELEASE IN THE CONTEXT OF THE CASE LAW OF POLISH PENITENTIARY COURTS – OUTLINE OF THE PROBLEM - Karol Siemaszko (Probacja, 2017)
This article presents the results of examining the case law of one of the Polish penitentiary courts regarding the grounds for refusal of conditional release pointed out in the statements of grounds of court orders. The author determined that the fact that the convicted person did not use the pass system was the most common argument invoked by the court. The author examines the arguments used by the court and at the same time assesses it in terms of compliance with applicable criminal law.